Studies on Phenolase Enzymes in Prawns 1. The Distribution and Physical Properties of Phenolases in Penaid Prawns - ANTONY, P. D.; NAIR, M. RAJENDRANATHAN (Fishery Technology, 1968)
The distribution of phenolases in certain species of Penaeid prawns has been studied. Attempts were made to locate the regions of maximum enzyme activity in the prawns. The relative dopase activity has been examined in extracts from head, tail, shell with cuticles and muscle. The head juice and tail extracts were found to register very high order of enzymic activity. Metapenaeus affinis, Metapenaeus monoceros and Penaeus indicus record comparatively higher enzymic activity than Parapenaeopsis stylifera and Metapenaeus dobsoni, No definite relationship has been found between the relative activity of the enzyme and size grade at least in one species examined. Experiments were done to determine the pH optima of the enzyme and the influence of pH on its deactivation. Exposure to higher temperatures upto 55C was shown to activate the crude enzyme considerably. The possible implications of the observations have been discussed.